EMPLOYEE PERFORMANCE IN THE NEXUS OF LEADERSHIP AGILITY, PERCEIVED ORGANIZATIONAL SUPPORT, ORGANIZATIONAL COMMITMENT AND READINESS FOR CHANGE - Suhermin, Suhermin; Rahayu, Rika; Zahro, Mar'atus; Shabrie, Wiwiek Srikandi; Suryawirawan, Okto Aditya (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
This research aims to explore the multifaceted impact of Industry 4.0 on employee performance through the involvement of leadership agility, perceived organizational support, organizational commitment, and readiness for change in PT Angkasa Pura I - Juanda, the company responsible for   overseeing airports in Indonesia. This study employs random sampling with specific inclusion criteria to gather the respondent. The data was collected from 150 employees of PT Angkasa Pura I - Juanda and analyzed using Partial Least Square through SmartPLS. The results show that the leadership agility significantly and positively influences the employee performance, individual readiness for change, and organizational commitment. Further, the perceived organizational support significantly and positively influences the organizational commitment and employee performance. Additionally, both the individual readiness for change and organizational commitment significantly and positively influences the employee performance. These results provide several implications related to the importance of   leadership agility, perceived organizational support, organizational commitment, and readiness for change in fostering employee performance.JEL: D23, M12, O15.